2018
DOI: 10.1177/1708538118798886
|View full text |Cite
|
Sign up to set email alerts
|

Functional prognosis of critical limb ischemia and efficacy of restoration of direct flow below the ankle

Abstract: Objective Patients with critical limb ischemia have serious systemic comorbidities and are at high risk of impairment of limb function. In this study, we assessed the prognostic factors of limbs after revascularization. Methods In this retrospective single-center cohort study, from April 2008 to December 2012, we treated 154 limbs of 121 patients with critical limb ischemia by the endovascular therapy-first approach based on the patients' characteristics. The primary end point was amputation-free survival. Sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…Our aggressive surgical first approach in Rutherford category 5 and 6 patients with extensive distal arterial disease appears justified in light of recent studies which have showed better results for bypass surgery compared to an endovascular approach. 10 We believe that revascularization is feasible in all patients with advanced CLTI, letting only permanently bedridden patients and patients with extensive gangrene or infection undergo primary amputation. Kalra et al reported amputation as a significant independent risk factor for higher long-term mortality.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Our aggressive surgical first approach in Rutherford category 5 and 6 patients with extensive distal arterial disease appears justified in light of recent studies which have showed better results for bypass surgery compared to an endovascular approach. 10 We believe that revascularization is feasible in all patients with advanced CLTI, letting only permanently bedridden patients and patients with extensive gangrene or infection undergo primary amputation. Kalra et al reported amputation as a significant independent risk factor for higher long-term mortality.…”
Section: Discussionmentioning
confidence: 98%
“…Besides relief of ischemic pain, ulcer healing, prevention of limb loss, and survival, functional recovery is a major objective of CLTI treatment, being strictly related to quality of life. 10 Infrainguinal bypasses are recommended for TASC D lesions. 12 The new Global Vascular Guidelines for treating CLTI, support surgical revascularization in those patients with extensive steno-occlusions of leg arteries and with WIfI stages 3 to 4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary outcomes included primary patency, limb salvage, and overall survival rate. Secondary outcomes included amputation-free survival, assisted primary patency, and functional status [ 7 ]. Outcomes were defined according to Rutherford reporting standards [ 2 ].…”
Section: Methodsmentioning
confidence: 99%